LONGITUDINAL STUDY ON LIVER FUNCTIONS IN PATIENTS WITH THALASSEMIA MAJOR BEFORE AND AFTER DEFERASIROX (DFX) THERAPY - Ashraf Tawfik Soliman; Mohamed Yassin; Fawzia AlYafei; Lolwa Al-Naimi; Noora Almarri; Aml Sabt; Vincenzo De Sanctis (Mediterranean Journal of Hematology and Infectious Diseases)
With regular blood transfusion and iron chelation therapy, most patients with thalassemia major (BTM) now survive beyond the third decade of life . Liver disease is becoming an important cause of morbidity and mortality in these patients. Chronic hepatitis and/or severe iron overload are important causes of liver pathology. Iron chelation with desferrioxamine (Desferal)  reduces excessive body iron, but its efficacy is limited by poor compliance and dose related toxicity. The recent use of Deferasirox (Exjade- DFX ), an  oral single dose therapy has improved the compliance to chelation therapy.